(untitled) (Raparin Journal of Humanities (RJH), 2024)
Youth people are the most important basis for the development of social and political systems and heritage change in different societies, so that their influence and dominance over various areas of life appears strongly, especially with regard to lifestyle, thinking, behavior and their point of view in the way of managing the political system. young people plays a powerful role in their Participation in the Political process, such as participation and representation in the electoral process, Pressure on the political system to achieve their demands, who were always been on the forefront of political, cultural and social changes and They were part of the process of changing and rebuilding political systems , when their demands are not met and they do not feel their presence in the political sphere, they do not allow political stability and continuity, so their presence and role appear strongly in society. this research is quantitative research, and the aim of the research is to display the active participation of young people in the political process. The research community is represented by universities and institutes in Erbil, sample research study from university and institute students through data collected from a data collection questionnaire. As a result of this research, we have found that 17.4 % members in student unions and youth organizations. However, 82.6% were not members of any organization, and only 29.4% of the participants were members of political parties. With regard to their active participation in the political process, it is interesting to note that 60.7% of the respondents do not have information about single-constituency and multiple-constituency system for the elections in the Kurdistan Region.